MINILAPAROTOMY AND OVARIAN DIATHERMY DRILLING FOR CLOMIPHENE RESISTANT POLY CYSTIC OVARIAN DISEASE - Abbasi, Aziz -un-Nisa; Sultana, Anwar; Izhar, Raeesa; Begum, Shamshad; Razaq, Sadia (Journal of Ayub Medical College Abbottabad, 2003)
Background: This study was carried out to determine the effectiveness and safety of minilaparotomy and ovarian drilling for sub fertile women with clomiphene resistant polycystic ovarian syndrome. Methods: During a 2 year period (August 2000 to August 2002) 16 patients with polycystic ovarian disease were managed by minilaparotomy and ovarian drilling by diathermy. All the patients underwent full infertility workup and then treated with cyclical clomiphene citrate for 6 months. Results: Six patients (37.5%) presented in age group 15-25 years. Eight patients (50.0%) were in age group 26-35 years. Only 2 (12.5%) patients presented in age group 36-44 years. Eleven (68.75%) patients had primary infertility. Five (31.25%) patients presented with secondary infertility. After treatment and 6 months follow up, ovulation occurred in 14 (87.5%) patients. Eleven (68.75%) women conceived pregnancy. Conclusion: Ovarian drilling is a powerful tool in the treatment of polycystic ovarian disease. Key Words: Polycystic ovarian Syndrome, Ovarian hyper stimulation syndrome, wedge resection, ovulation induction.